High school teachers’ perception on CLIL in an e-learning environment - Mateus-Gacha, Diana Rocío (My University, 2023)
The aim of this experimental research is to convey the perceptions of high school teachers of Content and Language Integrated Learning (CLIL) in an e-learning environment. Be that as it may, we begin with a brief overview of the bilingual curricula for learning a foreign language (FL) or a second language (L2) in high school programs using India and Colombia as examples. Followed by a definition of virtuality in education while describing types of digital learning and focusing on the impact of e-learning in CLIL, the nuances between the online spaces will be detailed and explained to set the context and move towards the core of the study. Using a small but significant sample of forty-six (46) surveys conducted online with CLIL teachers from more than six (6) different countries, and a combination of multiple choice and Likert-scale questions in a questionnaire, a quantitative study of teachers’ perspectives and perceptions of their CLIL teaching experiences was carried out. The findings of the data obtained to measure and analyse the views of CLIL teachers in a non-physical and remote context will be addressed. This evidence is used to support some techniques and educational processes that will be presented to satisfy the demands of students in online and remote environments. Along with an excerpt of comments from a limited group of teachers and facilitators, who shared their views in an open-ended interview, some qualitative findings were obtained to gain a deeper understanding of the impact of delivering online classes to high school learners based on the CLIL approach.
Keywords: Content and Language Integrated Learning (CLIL); e-learning; digital learning; high school; teachers’ perspectives; Máster Universitario en Educación Bilingüe